Designing Data and Information Architecture for Electronic-Based Government System - Cindy Han (International Journal of Educational Technology and Artificial Intelligence, 2022)
The study is part of an issue of women’s empowerment and child protection. It handles cases of violence against women and children. The objective is to develop data and information architecture and the domain of a government work unit (SKPD) for women’s empowerment and child protection. This paper studies implementing a model of object-oriented design and analysis based on the business process. The structured thinking method has a great revelation and helps create the data, information architecture, and domain.